Fresh Produce Markets as Direct Distribution Chanel for Organic Products in Republika Srpska - Sudarević, Tomislav; Galić, Jovana (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
The subject of this paper is the analysis of fresh produce markets in Republika Srpska as a direct distribution channel for organic products. The aim is to determine market share that fresh produce markets have, and to analyse consumer interest for the purchase of fresh organic products. The reviewed data and survey confirmed that the fresh produce markets are losing their market share, but the share they have is still significant. It is noticeable that fresh produce markets have no marketing activity, sellers promote their products mainly just by explaining the product characteristics. Consumers were questioned if they would purchase products more often from clearly marked stalls that offer organic fresh products only and if the products would have health and safety declarations and certificate of origin. Results showed significant correlation between these two variables, strenght 0,715, with answers of 88,5% of respondents that they would probably or for sure purchase more often if the first variable would be fulfilled, and 87,6% of them answering that they would probably or for sure purchase more often if the second variable would be fulfilled.